Stress Academic Dalam Mengerjakan Tugas Akhir Pada Mahasiswa Perantau: Adakah Pengaruh Self Efficacy Terhadap Stress academic ? - Aprilia, Yosi Harsa; Ishar, Meilia; Syah, Tansri Adzlan (Jurnal Ilmiah Psyche, 2024)
Academic stress is an individual’s perception of stressors originating from academics and seeing how the individual reacts consisting of physical, behavioral, cognitive and emotional reactions (Gadzella & Masten, 2005). Various factors cause academic stress in students including pressure, conflict, frustration, coercion, and change. This research aims to determine the effect of self efficacy on academic stress in completing final assignments among migrant students at state university (PTN) X in Lampung. The population in this study were students working on final assignments or theses, who came from outside Lampung or from West Sumatra who were residing or studying in Lampung (migrant) totaling 189 students. This research is a quantitative research with a samplingtechnique of 65 students. Data collection techniques use self efficacy and academic stress scales. The data analysis technique used in this research uses statistical methods with the help of IBM SPSS Statistics 25 software. The research results show r=0,669 with p0,000, which means there is a positive and significant relationship between self efficacy and academic stress. Self-efficacy makes an effective contribution of 44,8% to academic stress. Based on the research results, it can be concluded that there is a significant positive influence between self efficacy and academic stress in overseas students who are working on their final assignments at State University (PTN) X in Lampung. This means that the higher the self efficacy, the lower the academic stress behavior, and conversely the lower the self efficacy, the higher the academic stress behavior in overseas students who are working on their final assignments. The effective contribution of the self-efficacy variable is 44,8% to academic stress and the rest is influenced by variables outside this research.